1997
DOI: 10.1002/(sici)1099-1581(199705)8:5<297::aid-pat649>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Characterization of Conjugates of Nucleic Acid Probes and 6-Aminoglucose-based Polymers

Abstract: Homopolymers based on 6‐deoxy‐6‐methacryloylamido‐d‐glucopyranose (6‐aminoglucose), obtained by radical‐initiated polymerization, were used as reactive polymeric supports to tether oligodeoxyribonucleotides (ODNs) in order to make oligonucleotide–polymer conjugates of potential applications in diagnostics. The reducing ends of the homopolymers, used as self‐protected groups during the radical polymerizations, served as reactive groups for the covalent attachment of 5′‐amino‐modified oligodeoxyribonucleotides v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…The covalent binding of Hepatitis B virus DNA probes (HBV ODNs) was performed according to a general procedure previously established at CNRS-bioMØrieux laboratory [8] for polymer chains bearing glucose residues Scheme 3. synthesized by conventional free-radical polymerization. This binding is based on a reductive amination reaction between the amino-terminated ODNs and the aldehyde function present on the acyclic form of the galactose moieties along the deprotected poly(GVE) chains (Scheme 4).…”
Section: Covalent Binding Of Oligonucleotidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The covalent binding of Hepatitis B virus DNA probes (HBV ODNs) was performed according to a general procedure previously established at CNRS-bioMØrieux laboratory [8] for polymer chains bearing glucose residues Scheme 3. synthesized by conventional free-radical polymerization. This binding is based on a reductive amination reaction between the amino-terminated ODNs and the aldehyde function present on the acyclic form of the galactose moieties along the deprotected poly(GVE) chains (Scheme 4).…”
Section: Covalent Binding Of Oligonucleotidesmentioning
confidence: 99%
“…This property has long been used to perform the covalent binding of NH 2 -bearing molecules such as proteins [6,7] or nucleic acid probes. [8] Because of such specific properties, many studies have been dedicated to the synthesis of polymers containing saccharidic residues, usually by polymerization of the corresponding monomer, whether via a conventional free radical, cationic or anionic process. [9][10][11][12][13][14][15] Recently, new routes to glycopolymer synthesis have been described, namely via controlled polymerization mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Poly (MA-alt-DVE), known as pyran copolymer is one of the well known bioengineering polymers having a wide range of biological activity. It processes antitumor, antiviral, antibacterial and antifungal activities, induces interferon formation, and acts as an anticoagulant and anti-inflammatory agent [8,[12][13][14][15][16][17]. Hirano et al [18,19] reported that the poly (MA-alt-DVE) conjugated with bovine erythrocyte superoxide dismutase (SOD) is resistant against the proteolytic enzymes in serum, and shows a prolonged half-life in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…They established an increase in half-life after intravenous injection, as well as its decreased immunogenicity [19]. It was demonstrated that the copolymer-SOD conjugate shows anti-inflammatory effect against rat re-expansion pulmonary edema at the first step of leukocyte adhesion [15]. Maeda [20] discussed the development and therapeutic potential of prototype macromolecular drugs for use in cancer chemotherapy an artificial bioconjugate of neocarzinostatin (NCS) and poly(maleic acid-alt-styrene) copolymer.…”
Section: Introductionmentioning
confidence: 99%
“…To date, aliphatic amino groups have been extensively used for this purpose. Attachment of this group to one end of the oligonucleotide allows for facile reaction with incoming functional groups in the form of electrophiles (e.g., activated carboxylic groups [10][11][12], isothiocyanates [13,14], alkylating agents and aldehydes with further reduction by sodium borohydrate [15,16]). …”
Section: Introductionmentioning
confidence: 99%